Suppressing Effects of Down-regulating DNMT1 and DNMT3b Expression on the Growth of Human Cholangiocarcinoma Cell Line - 左石 罗剑 刘民锋 徐立宁 董泾青 郭伟 邹声泉 (Journal of Huazhong University of Science and Technology. Medical sciences, 2008)
Hypermethylation in the promoter region is an important epigenetic mechanism for the transcriptional repression of a number of cancer-associated genes, and over-expression and/or increased activity of DNA methyltransferases are considered to be the main cause of promoter hypermethylation. In order to explore the roles of two methyltransferase members （DNMT1 and DNMT3b） in the cholangiocarcinoma tumorigenesis, antisense eukaryotic expression plasmid of DNMT1 and DNMT3b gene was constructed respectively, and were co-transfected into the human cholangiocarcinoma cell line QBC-939 to observe their biological effects on the cell growth and proliferation ability, apoptosis, cell cycle alteration, and the tumorigenesis ability in the subcutaneous tissue of nude mouse. The results demonstrated that co-transfection with antisense eukaryotic expression plasmid of DNMT1 and DNMT3b gene and single transfection with antisense eukaryotic expression plasmid of DNMT1 gene can suppress the growth and proliferation of QBC-939, block the cell cycle at G1 phase, increase the apoptosis rate, minimize the tumor size in the subcutaneous tissue of nude mouse. The suppressing biological effect of co-transfection is stronger than single transfection with antisense DNMT1. Meanwhile, single transfection with antisense eukaryotic expression plasmid of DNMT3b gene has no effects on the biological characteristics of QBC-939. This study suggests that DNMT1 gene plays a key role in DNA methylation and DNMT3b gene may act as an accessory to support its function in inactivation of tumor suppressor genes. Combination DNMT1 and DNMT3b will increase their biological effects and have the synergistic effect on suppressing the growth of human cholangiocarcinoma cell line QBC-939.